Incorporating a Class Analysis within the National Question: Rethinking Ethnicity, Class, and Nationalism in Cyprus - Bozkurt, Umut; Trimikliniotis, Nicos (Routledge Journals, Taylor & Francis Ltd, 2014)
This article has two main aims. First, it aims to challenge the widespread narrative in Cyprus studies that presents ethnic identities as historically inevitable and natural. Rather, identities need to be conceptualized as socially constructed. The second aim of this article is to problematize the argument that ethnic or national groups are homogenous actors. It underlines the need to deconstruct these supposedly unitary actors by making use of a class-based conceptualization of the state. By using such a conceptualization, the article will focus on the period between 1878 and 1974. It will start with a concrete analysis of the class structure in the Cypriot society and then will trace how different classes in both communities positioned themselves vis-a-vis political structures of power and how these positionings paved the way to the division of the island.
Keywords: State